Assessment of Heavy Metals Contamination of Water and Cupscale Grass (Sacciolepisafricana) along the Epie Creek in Bayelsa State, Nigeria - Timi, Tarawou; Young, Erepamowei; Ayobami, Aigberua (Journal of Plant and Animal Ecology, 2019)
This study was conducted to investigate the concentration of three heavy metals; iron, chromium and lead in surface water and plant (Sacciolepisafricana) tissues along the Epie creek. This was aimed at determining the heavy metal loading of surface waters and the extent of bioaccumulation in the most prevalent grass species found growing within the river course. Metals were determined using atomic absorption spectrophotometer. Result of water analysis recorded the least and most significant iron concentrations of 3.42 ± 0.06 mg/L and 12.06 ± 0.06 mg/L for Agudama and Edepie axis respectively. Contrastingly, water samples showed chromium and lead levels which were below their instrument measurable limits. Consequently, lead (Pb) and chromium (Cr) levels were within WHO permissible limits, while iron (Fe) exceeded regulatory standard for water samples collected from all field locations. Similarly, iron recorded elevated iron concentrations in plant (cupscale grass) with the least amount being revealed for Igbogene stem (196.63 ± 5.21 mg/kg), and the most concentration been reflected for Edepie root sample (9,423.17 ± 48.55 mg/kg). Even though iron levels prevalently exceeded recommended threshold in plants, the stem were mostly within limit for iron. The only grass sample depicting significant lead amount (0.34 mg/kg) was the stem section collected at Akenfa location. Evidently, metals were least stored in plant stems and most bioaccumulated in plant roots. Furthermore, Cr and Fe are the only significantly correlating metals in plants (r = 0.700, p < 0.01). Overall, the increasing level of Fe in the water environment is further indication of the impact of unregulated dumping of scraps and domestic waste along the creeks embankment.
Keywords: Anthropic; Heavy metals; Contamination; Cupscale grass; Epie Creek